Etiology of Acute Otitis Media in Children Less Than 5 Years of Age: A Pooled Analysis of 10 Similarly Designed Observational Studies. Issue 3 (March 2017) - Van Dyke, Melissa K.; Pirçon, Jean-Yves; Cohen, Robert; Madhi, Shabir A.; Rosenblüt, Andrés; Macias Parra, Mercedes; Al-Mazrou, Khalid; Grevers, Gerhard; Lopez, Pio; Naranjo, Laura; Pumarola, Felix; Sonsuwan, Nuntigar; et al.
Abstract : Background: Acute otitis media (AOM) is an important cause of childhood morbidity and antibiotic prescriptions. However, the relative importance of the well-known otopathogens, Streptococcus pneumoniae (Spn) and Haemophilus influenzae (Hflu), remains unclear because of a limited number of tympanocentesis-based studies that vary significantly in populations sampled, case definitions and heptavalent pneumococcal conjugate vaccine use. Methods: We conducted a pooled analysis of results from 10 AOM etiology studies of similar design, the protocols of which were derived from a common protocol and conducted in children 3 months to 5 years of age in different countries. Generalized estimating equations were used to account for within-study correlations. Results: The majority, 55.5% (95% confidence interval: 47.0%–65.7%) of 1124 AOM episodes, were bacterial pathogen positive: 29.1% (24.8%–34.1%) yielded Hflu and 23.6% (19.0%–29.2%) Spn. Proportions of Hflu and Spn were higher and lower, respectively, in heptavalent pneumococcal conjugate vaccine–vaccinated children. Hflu and Spn were each isolated from 20% to 35% of children in every 1-year age range. Hflu was less likely to be isolated from first (vs. subsequent) episodes [relative risk (RR): 0.71 (0.60–0.84)]. Spn was more often isolated from sporadic (vs. recurrent) cases [RR: 0.76 (0.61–0.97)]; the opposite was true for Hflu [RR: 1.4 (1.00–1.96)]. Spn cases were more likely to present with severe (vs. mild) symptoms [RR: 1.42 (1.01–2.01)] and Hflu cases with severe tympanic membrane inflammation [RR: 1.35 (1.06–1.71)]. Conclusions: Spn and Hflu remain the leading otopathogens in all populations examined. While associated with overlapping symptoms and severity, they exhibit some differences in their likelihood to cause disease in specific subpopulations. Abstract : Supplemental Digital Content is available in the text.